Potential Emphasis of Formulated Herbal Cream on Wound Healing - Shivhare, Yogesh; Jain, Alok Pal (Asian Journal of Pharmaceutical Research and Development, 2020)
Aim: The present study was to formulate and evaluate the herbal cream comprising extracts of different medicinal plants. Experimental: The aqueous extract of all selected plants (Chenopodium album, Coccinia indica, Momordica dioica, Praecitrullus fistulosus and Trichosanthes dioica) were prepared by successive solvent extraction using soxhlet apparatus. Topical herbal cream was formulate and examined on different parameters like colour, consistency, pH, viscosity, spreadability and stability. Pharmacological evaluation of formulated herbal cream was done with excision and incision wound models. Results and Conclusion: Based on the resultant findings obtained from the different evaluation parameters, it can be concluded that prepared herbal formulation was stable and safe to use in wound healing activity.